Global research trends and focus on immunotherapy for endometrial cancer: a comprehensive bibliometric insight and visualization analysis (2012-2024) - Xu, Yachen; Wang, Tao; Liang, Xiaojing; Yang, Jie; Zhang, Yuxiang; Bao, Shan (Frontiers in Immunology, 2025)
BackgroundThis study conducted a novel systematic bibliometric and visualization analysis of global literature on immunotherapy for endometrial cancer (EC) to explore dynamic trends, research hotspots, and emerging topics, providing valuable references for future research.MethodsArticles and reviews on EC immunotherapy published between 2012 and August 2024 were retrieved from the Web of Science Core Collection (WoSCC). Bibliometric tools, CiteSpace and VOSviewer, were used to analyze clustering patterns and research dynamics.ResultsA total of 861 articles were contributed by 5,331 authors from 1,392 institutions across 58 countries or regions, involving 1,823 keywords. China demonstrated outstanding performance in this field, contributing over 40% of the total publications and ranking first in publication volume. However, the total citation counts for publications from China lags that of the United States, highlighting the latter’s leading position and areas for further improvement in China’s research efforts. The University of Texas Medical Anderson Cancer Center and Nanjing Medical University were the two institutions with the highest number of publications. In terms of authorship, research teams led by Bosse, Tjalling, and Creutzberg, Carien L made significant contributions to advancing the field. Among individual publications, the work by Talhouk et al. achieved the highest average annual citation count of 70.88, demonstrating its profound impact. In terms of journals, Gynecologic Oncology emerged as a pivotal academic platform, publishing numerous articles and achieving the highest co-citation frequency. Additionally, Frontiers in Oncology, Frontiers in Immunology, and Frontiers in Genetics have become some of the most active and rapidly developing journals in recent years. Research hotspots are concentrated on themes such as the “Tumor Immune Microenvironment”, “Immune Checkpoint Inhibitors”, and “Targeted Therapy”. Recent trends and frontier research focus on the combined application of immune checkpoint inhibitors with other therapies, research on the application of nanotechnology in immunotherapy, and the integration of artificial intelligence to enhance precision medicine. Additionally, efforts are increasingly directed toward advancing various immunotherapy strategies from basic research to clinical applications.ConclusionsThis comprehensive analysis reveals rapid advancements and significant potential in EC immunotherapy. Strengthening international collaboration and addressing barriers in the translation of research to clinical practice will drive further progress in this promising field.